2006
DOI: 10.1007/s10552-005-0515-z
|View full text |Cite
|
Sign up to set email alerts
|

Decline in Cervical Cancer Incidence and Mortality in New South Wales in Relation to Control Activities (Australia)

Abstract: The substantial reduction of cervical cancer incidence and mortality in NSW over the last 3 decades is associated with important health service interventions that relate to control of cervical cancer, particularly the implementation of a population-based organised cervical screening program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 21 publications
1
24
0
Order By: Relevance
“…Several studies demonstrated that cervical canser screening by Pap test reduces mortality rates. (Nygard et al, 2002;Abed et al, 2006;Aklimunnessa et al, 2006;Taylor et al, 2006). Currently, there is no organized population-based screening program available for the whole World.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies demonstrated that cervical canser screening by Pap test reduces mortality rates. (Nygard et al, 2002;Abed et al, 2006;Aklimunnessa et al, 2006;Taylor et al, 2006). Currently, there is no organized population-based screening program available for the whole World.…”
Section: Discussionmentioning
confidence: 99%
“…3 This programme has been highly successful in reducing cervical cancer incidence and mortality in Australia, 3,4 including in New South Wales (NSW), the most populous Australian state. 5 The current recommended cervical screening policy in Australia is routine screening with Pap smears every two years for women who have ever been sexually active and have no symptoms or history suggestive of cervical pathology. 4,6 During the five year period (1 July Integral to the NSW Cervical Screening Program is the opt-off Pap Test Register (PTR) which (1) records all Pap tests and cervical histology tests and their results on NSW women; (2) acts as a safety net for screening reminders for women who are overdue for a subsequent test; and (3) is charged with implementing a programme of quality assurance at all steps along the screening pathway.…”
Section: Introductionmentioning
confidence: 99%
“…To exemplify, from a brief literature search we suspect that the results of Yu et al, 2006 may be significantly affected by the artefactual degree-of-spread data 5 and other publications perhaps less so. 3,12 Accordingly, we strongly recommend that researchers who may have used degree-of-spread information provided by the NSW CCR in the past review carefully the implications of this report in relation to any results that they may have reported, or with regard to any policies that may have emanated from such results.…”
Section: Discussionmentioning
confidence: 99%
“…Two major uses of the degree-of-spread data are to evaluate the effectiveness of screening programs [1][2][3] and to analyse the survival of patients by extent of disease at first presentation. 4,5 Degree-of-spread represents the most aggressive extent of the disease based on diagnostic and therapeutic evidence.…”
mentioning
confidence: 99%